Management of red needle cast caused by Phytophthora pluvialis a new disease of radiata pine in New Zealand - Ganley, R.J.; Williams, N.M.; Rolando, C.A.; Hood, I.A.; Dungey, H.S.; Beets, P.N.; Bulman, L.S. (New Zealand Plant Protection, 2014)
Ten years ago there were no known foliar diseases caused by Phytophthora on pine trees worldwide Since then two significant Phytophthora diseases have emerged on radiata pine one of which is only known in New Zealand Red needle cast is a disease caused by the pathogen Phytophthora pluvialis which is thought to have originated from northwestern USA This paper reviews the challenges the New Zealand forestry industry faces when dealing with this disease and evaluates the management options such as chemical control biological control and breeding programmes being investigated to minimise its effect on forest productivity The distribution of the pathogen in New Zealand and research that shows bark logs and wood are free of the pathogen therefore unlikely to pose biosecurity threats through trade in these products are also outlined